Hubungan dukungan keluarga dengan perilaku seksual remaja di SMK Kesehatan IT Al Hidayah Gununghalu Tahun 2022 - Siti Asma Nurul Fazila; Eka Rokhmiati; Yeni Kyoto (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Background: Adolescence is a time when many changes occur, including biological, psychological and social spiritual changes, one of the biological changes is sexual desire, one of the causes of adolescent sexual behavior is lack of family supervision and attention. This study aims to determine the relationship between family support and adolescent sexual behavior. Objective: In this study, researchers want to find out whether there is a relationship between family support and sexual behavior in adolescents. Method: This type of research is quantitative using a descriptive correlation research design carried out using a cross sectional approach. This research was conducted at Al-Hidayah Gununghalu IT Health Vocational School in 2022. The population in this study were all teenage students with a sampling technique using total sampling. The instrument in this research was a questionnaire. Data analysis using Chi Square.